CI/CD in a cloud native world (O'Reilly Media, 2019)
"Systems may be going cloud native, but your CI/CD may not be keeping up. It's challenging to make sure the environments you test and develop on have parity with the environments you deploy to, and you also have to keep track of what you deployed where and when you deployed it. Moving your systems to more complicated environments impacts your entire software supply toolchain. Christie Wilson (Google) explains the challenges of testing, building, and deploying in a cloud native landscape. She examines how tools and systems available today meet these challenges, the benefits you get from cloud native CI/CD, and what's still to be solved. This session was recorded at the 2019 O'Reilly Open Source Software conference in Portland."--Resource description page